N-Laplacian critical problem with discontinuous nonlinearities - Tiwari Sweta (Advances in Nonlinear Analysis, 2015)
In this paper, we study the existence of a solution of the N-Laplacian critical problem with discontinuous nonlinearity of Heaviside type in a smooth bounded domain with respect to a positive parameter λ.